Port Injection Of Biomass Producer Gas From Downdraft Gasifier In A Diesel Engine - Hassan, Suhaimi (2011)
Producer gas (PG), generated from thermo-chemical conversion process of biomass gasification has been proven to be used as an alternative fuel for internal combustion engine. However, major problems of PG when used as fuel in internal combustion engine are loss of power or engine derating and high exhaust emissions due to incomplete combustion. The most possible reasons are due to low heating value of PG itself and low energy density of PG-air mixture as compared to other alternative gaseous fuel. Based on literature studies, the main factors influencing power output from internal combustion engine fuelled with PG, particularly diesel engine are compression ratio, heating value of PG and the way of air is introduced into the engine cylinder.